Overview of Comorbidities in Mothers Delivering by Caesarean Section - Nadya Putri Berliana Fatati Yusuf; Sulastri Sulastri; Nuri Indah Sari (Indonesian Journal of Global Health Research, 2026)
Caesarean section (CS) is an obstetric procedure that is increasingly common in Indonesia and is often influenced by the presence of comorbidities in pregnant women. Understanding the factors that cause CS based on the Five P concept (Power, Passage, Passenger, Position, and Psyche) is important for improving the quality of maternity nursing care. To determine the characteristics of comorbidities in mothers giving birth with indications for CS at Hidayah Boyolali General Hospital based on the Five P concept. This study used a quantitative descriptive design with a retrospective approach. A sample of 118 mothers who gave birth by CS was taken using total sampling from medical records for the period July 2024–September 2025. Data was collected by recording the reasons why patients underwent CS, which can be viewed in the Hospital Management System. Data were analysed descriptively and quantitatively to display the frequency distribution of each causative factor. The most common concomitant factor was Power (43.2%), followed by Passage (27.1%), Psyche (12.7%), Passenger (11.1%), and Position (5.9%). Most mothers were aged 21–30 years and had full-term pregnancies (37–40 weeks). The Power factor was the dominant cause of CS, highlighting the importance of strengthening contraction monitoring, physical readiness, and psychological support. The application of a holistic approach in maternity nursing is expected to reduce the rate of medically unindicated CS.